Investigating The Views Of Social Studies Teacher Candidates On Sustainable Development - Değirmenci, Yavuz; Gül, Dilek (Fırat University, 2024)
The concept of sustainable development, which has been at the forefront of the agenda of countries in recent years, has an increasing importance. However, this concept manifests itself in a wide range from education, health, economy, environment, social areas to individual life. Considering the developments in the global and regional scale today, the concept of sustainable development is seen as important for a more livable world and future; education also has important duties in increasing sensitivity and awareness on this issue. The aim of this study is to examine the views of pre-service social studies teachers who have taken undergraduate courses on sustainable development towards this concept. The research was designed according to qualitative method. Interview technique was used as a data collection tool. Descriptive analysis was used to analyse the data. According to the results of the research; the participants associated the concept of sustainability mostly with the use of natural resources and emphasised the importance of this concept for future generations. In addition, they stated that it is important not to waste resources and to use them economically for sustainability, and that education in this concept can be effective in creating awareness and consciousness in individuals.

Son yıllarda ülkelerin gündeminde ön planda yer alan sürdürülebilir kalkınma kavramı giderek artan bir öneme sahiptir. Bununla birlikte eğitimden, sağlığa, ekonomiden, çevreye, sosyal alanlardan bireysel yaşama kadar bu kavram geniş bir yelpazede kendini göstermektedir. Günümüzde küresel ve bölgesel ölçekte yaşanan gelişmeler de dikkate alındığında sürdürülebilir kalkınma kavramı daha yaşanabilir bir dünya ve gelecek için önemli görülmekte; bu konuda duyarlılığı ve farkındalığı artırmada eğitime de önemli görevler düşmektedir. Bu çalışmanın amacı sürdürülebilir kalkınma ile ilgili lisans düzeyinde dersler almış sosyal bilgiler öğretmen adaylarının bu kavrama yönelik görüşlerini incelemektir. Araştırma nitel yönteme göre tasarlanmıştır. Veri toplama aracı olarak görüşme tekniği kullanılmıştır. Verilerin analizinde ise betimsel analize yer verilmiştir. Araştırma sonuçlarına göre; katılımcılar sürdürülebilirlik kavramını daha çok doğal kaynak kullanımı ile ilişkilendirerek, bu kavramın gelecek nesiller adına önemini vurgulamışlardır. Ayrıca sürdürülebilirlik adına kaynakların israf edilmemesi ve tasarruflu kullanılmasının önemli olduğunu, bu kavram özelinde eğitimin ise bireylerde farkındalık ve bilinç oluşturmada etkili olabileceğini belirtmişlerdir.
SOSYAL BİLGİLER ÖĞRETMEN ADAYLARININ SÜRDÜRÜLEBİLİR KALKINMAYA İLİŞKİN GÖRÜŞLERİNİN İNCELENMESİ
Keywords: Social and Humanities Education (Excluding Economics; Business and Management); Sosyal ve Beşeri Bilimler Eğitimi (Ekonomi; İşletme ve Yönetim Hariç)